Da horda ao Leviatã: um percurso pelos lugares constitutivos do humano - Leirias, Fabiano Barros Vasconcelos (2017)
In many fields of knowledge, has been appointed the mutation and worked for the social bond today, as well as various effects of this phenomenon. This mutation, on which huddled philosophers, sociologists, psychoanalysts, political scientists, among others, occurs as a result of the deletion of the third place, which was occupied for many centuries the divine dimension. From the modern period, with the gradual decline of hegemonic models and the rise of religious doctrine as scientific activity of choice for acquiring knowledge, the fall of the deity as a reference, brought himself to the rejection of the third place. Therefore, this paper proposes to do a reading of the social bond in the way it is today, from the joint that is created between two works dedicated to the question of the emergence of human social ties and social institutions: the book Totem and Taboo of Freud, published in 1913 and Leviathan, written by Thomas Hobbes in 1651. By virtue of the relationships between texts, two social effects of the mutation are analyzed: the increasing use of the legal sphere as a means of social mediation and the emergence of the physical body, taken at the forefront of its biological dimension.